1994
DOI: 10.1159/000267510
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cataract Using the Retroillumination Module of the Nidek EAS-1000 Anterior Segment Analysis System

Abstract: Cortical and posterior subcapsular (PSC) cataracts are best quantified by a retroillumination method. We have used the Nidek EAS-1000 camera system to document such cataracts and have investigated how variability from operator input may be minimised when analysing retroillumination photographs. We then used our method to quantify the reproducibility of (i) image analysis and (ii) the system as a whole. A total of 99 eyes from 70 patients with either cortical or posterior subcapsular cataracts were photographed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Analysis was done in masked fashion with no knowledge o f which images were being analysed except where re-analysis was necessary for some retroillumi nation pictures because o f differing pupil diameters. Retroillumination images were analysed according to a protocol previously described [20]. If there was a dif ference between initial and 6-month pictures, the smaller of the two diameters was used for both pic tures.…”
Section: Patients and M Ethodsmentioning
confidence: 99%
“…Analysis was done in masked fashion with no knowledge o f which images were being analysed except where re-analysis was necessary for some retroillumi nation pictures because o f differing pupil diameters. Retroillumination images were analysed according to a protocol previously described [20]. If there was a dif ference between initial and 6-month pictures, the smaller of the two diameters was used for both pic tures.…”
Section: Patients and M Ethodsmentioning
confidence: 99%
“…Previous studies have shown the EAS-1000 t o be highly reproducible112 in lenses with varying degrees of opacity. 2 We have used custom-written standardized soft-ware for image analysis to minimize observer variation. For the longitudinal analyses t o be used by the VECAT Study it was necessary t o examine the repeatability of the measurements utilizing this software in lenses with little or no significant opacity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also indicated the capture and analysis of Nidek EAS-1000 images to be reproducible. 1 2. Analysis of components of variance7 is presented inTable 1.…”
mentioning
confidence: 99%